Inhibition of nitric oxide synthesis by NG-nitro-L-arginine methyl ester (L-NAME): requirement for bioactivation to the free acid, NG-nitro-L-arginine. - Pfeiffer, S. (1996)
1. The L-arginine derivatives NG-nitro-L-arginine (L-NOARG) and NG-nitro-L-arginine methyl ester (L-NAME) have been widely used to inhibit constitutive NO synthase (NOS) in different biological systems. This work was carried out to investigate whether L-NAME is a direct inhibitor of NOS or requires preceding hydrolytic bioactivation to L-NOARG for inhibition of the enzyme. 2. A bolus of L-NAME and L-NOARG (0.25 micromol) increased coronary perfusion pressure of rat isolated hearts to the same extent (21 +/- 0.8 mmHg; n = 5), but the effect developed more rapidly following addition of L-NOARG than L-NAME (mean half-time: 0.7 vs 4.2 min). The time-dependent onset of the inhibitory effect of L-NAME was paralleled by the appearance of L-NOARG in the coronary effluent. 3. Freshly dissolved L-NAME was a 50 fold less potent inhibitor of purified brain NOS (mean IC50 = 70 microM) than L-NOARG (IC50 = 1.4 microM), but the apparent inhibitory potency of L-NAME approached that of L-NOARG upon prolonged incubation at neutral or alkaline pH. H.p.l.c. analyses revealed that NOS inhibition by L-NAME closely correlated with hydrolysis of the drug to L-NOARG. 4. Freshly dissolved L-NAME contained 2% of L-NOARG and was hydrolyzed with a half-life of 365 +/- 11.2 min in buffer (pH 7.4), 207 +/- 1.7 min in human plasma, and 29 +/- 2.2 min in whole blood (n = 3 in each case). When L-NAME was preincubated in plasma or buffer, inhibition of NOS was proportional to formation of L-NOARG, but in blood the inhibition was much less than expected from the rates of L-NAME hydrolysis. This was explained by accumulation of L-NOARG in blood cells. 5. These results suggest that L-NAME represents a prodrug lacking NOS inhibitory activity unless it is hydrolyzed to L-NOARG. Bioactivation of L-NAME proceeds at moderate rates in physiological buffers, but is markedly accelerated in tissues such as blood or vascular endothelium.